The Intelligent Vacation Planner System using Ant Colony Optimization - Peh, Perly Thai Ee; Choo, Yun Huoy; Mohd Aboobaider, Burhanuddin (2010)
Due to the rapid demand on travelling, tourism has been identified as one of the key areas in industrial strategic planning by the Malaysian government. One of the main problems in promoting tourism nowadays is the lack of vacation planning system that can help holiday planners to plan their schedules. Thus, this paper proposes an Intelligent Vacation Planner System (IVPS) which contains an intelligent module that can optimize the travelling route based on user preference. The primary users of the system will be the potential tourists visiting Malaysia and the administrators who manage the IVPS system. The system was implemented with object oriented software engineering methodology on a 3-tier web based architecture. The HTML, Javascript, Java, SQL and Java Server Page (JSP) were used in developing the IVPS system. This paper discusses on the implementation of Ant Colony technique to optimize the travelling route or itinerary for the IVPS system. It generates customised travelling plan based on selected destinations, departure points, transport type, travel group size, accommodation type and travel duration. The system will be expected to promote Malaysian tourism by offering cost effective tour packages in terms of optimized travelling routes and time. For future improvement, the implementation of ant colony optimization technique will be compared to other optimizers in travelling route optimization. Further work will also focus on improving the functionality of the administration and maintenance of the proposed system.